Polyketides and alkaloids from the fungus Aspergillus Fumigatus YB4-17 and ent-Fumiquinazoline J induce apoptosis, paraptosis in human hepatoma HepG2 cells - Wang, Huannan; Sun, Lixiang; Ma, Xueyang; Jin, Shihao; Xi, Yidan; Sai, Chunmei; Yan, Maocai; Cheng, Zhongbin; Zhang, Zhen (Frontiers in Pharmacology, 2024)
Seven polyketides (1  7), including a new diphenyl ether derivative (1), along with fourteen known alkaloids (821), were isolated from a marine oyster-derived fungus Aspergillus fumigatus YB4-17. The structure elucidation of these compounds was conducted via NMR spectroscopic data and MS data analysis. The absolute configuration of compounds 11 was determined for the first time by comparing experimental electronic circular dichroism (ECD) spectra with the calculated data. The biological evaluation of these metabolites revealed that compound 11 selectively inhibited the proliferation of HCC HepG2 cells with negligible toxicity to normal cells. Mechanism study indicated that compound 11 induced apoptosis and paraptosis in HepG2 cells, providing a novel therapeutic perspective for HCC treatment.Circinophoric acid ethyl ester (1) was obtained as a white powder. The chemical formula was assigned as C20H22O8 by HRESIMS ([M + Na]  m/z 413.1235, calcd for C20H22O8Na + , m/z 413.1212) and 13 C NMR spectroscopy (Figure S2), requiring ten degrees of unsaturation.Summation of the integrals from the 1 H NMR spectrum (Figure S1) indicated the presence of a total of 21 protons, indicating the existence of one hydroxy group. Further examination of the 1 H NMR spectrum indicated the presence of five methyls including a methyl triplet (H 1.23, J = 7.1Hz), three methoxys (H 3.76, 3.68, 3.61), and an aromatic methyl (H 2.15). The observation of two meta-coupled doublets (H 6.76, 6.73) and two broad singlets (H 6.51, 5.79) in the aromatic region revealed the presence of at least two benzene rings. The quartet integrated for two protons at 4.21 was coupled to the methyl triplet at 1.23, indicating the presence of an ethoxy group. The